Design and development of a smart used car recommendation system - Te, Kay Hoe (2025)
This project focuses on developing a recommendation system dashboard project for academic purpose, specifically within the field of machine learning. The primary goal is to implement recommendation system algorithms that provide personalized used car recommendations for Malaysian users. This project is required as Malaysia faces a few challenges in the used car market. These problems include choice overload overwhelming users and lack of used car recommendation system tailored to Malaysians looking for used cars. To understand and address these challenges, reviews of past studies related to Malaysian used car market and recommendation system has been done. As a result, this dashboard will use combination of few approaches such as content filtering and clustering to ensure accurate recommendations to users. Technologies that are commonly used in recommendation systems such as Python will also be used for the development process. This project aims to contribute to local used car market by ensuring transparency and healthy interaction between buyers and authentic used car dealers. The output of this project should be able to collect preferences from user, then provide recommendations based on these preferences.